Effect of Pack-Boriding on the Tribological Behavior of Hardox 450 and Hituf Steels - Aktas, Bulent; Toprak, Mehmet; Calik, Adnan; Tekguler, Ali (de Gruyter Poland Sp Z O O, 2020)
In this study, Hardox 450 and HiTuf steels were boronized by pack-boriding method at 800, 900, and 1000 degrees C for 5 h. The phases, microstructure, hardness, and wear behavior of boride layers formed on the surface of samples were investigated using XRD, SEM, Micro-Vickers hardness testers, and a pin-on-disc tribotester, respectively. XRD analysis showed that both FeB and Fe2B phases were formed in the bonded area of Hardox 450 steel, but only Fe2B phase occurred in the boride layer of the HiTuf steel. Micro-Vickers hardness results indicated that the hardness values of the boride layer decreased from the column-shaped structure to towards the matrix in both of Hardox 450 and HiTuf steels. Furthermore, the wear test results showed the coefficients of friction (COF) decreased significantly in the borided samples. The COF of the unbonded Hardox 450 steel was reduced considerably from 0.29 to 0.02 by boriding treatment. Similarly, the COF of unborided HiTuf steel was significantly diminished from 0.16 to 0.04 by bonding treatment. In conclusion, the results of this study have indicated that the wear resistance of Hardox 450 and HiTuf steels can be improved by packbonding.
Aktas, Bulent/0000-0002-9396-1534
Keywords: Hardox 450 and Hituf Steel; Pack-Boriding; Friction; Wear